The impact of stock market liquidity on business cycles - van Hees, Thomar Pepijn (2019)
It is a common empirical finding that stock market liquidity tends to dry up before a recession. This thesis estimates the effect of different liquidity measures on business cycles. Using seven different liquidity measures, separated into four categories that differ in their nature of measuring liquidity, it is shown that the effect of liquidity on GDP growth and recessions differ among measures and categories in the United States for the period 1952-2011. The analysis consists of a Granger-causality test, in-sample predictions, and out-of-sample forecasting. The findings indicate that the market-impact and price-based measures contain no economic information about business cycles. However, volume-based measures show a significant relationship with both GDP growth and recessions, whereas transaction costs measures only show a relationship with short-term growth. Furthermore, the findings indicate that the illiquidity ratio dominates in forecasting recessions, several measures provide equal predictive accuracy of forecasting GDP growth. Overall, the results show that stock market liquidity provides information about business cycles and that this information varies with different liquidity measures.